Residu Deltamethrin Terlacak pada Hati Ayam Pedaging yang Dipasarkan di Yogyakarta (DETECTION OF DELTAMETHRIN RESIDUE IN BROILER LIVER TRADED IN YOGYAKARTA) - Satria, Gagak Donny; Wijayanti, Agustina Dwi; Sari, Puspa Wikan; Setiawan, Dwi Cahyo Budi; Hakimah, Nisa; Rahmawati, Annisa (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
The consumer assurance to get safe, hygienic, whole, and halal food is an important concern. Analysisof chemical residue is one of some ways  to examine food safety. The objective of this research was to detectdeltamethrin residue in broiler liver sold in Yogyakarta, Indonesia. The isocratic HPLC method was usedin this research, using Shimadzu 6.1, 80% of Acetonitrile in Aquabides as mobile phase, with 1ml/minutesof flow rate. C-18 was used as column and the wavelength of UV-Vis detector was 270 nm. The result of theresearch was get from HPLC’s analyses. Deltamethrin’s peak area would be presented in retention time 8-12minutes with specific profile of curve. The result of the research showed that deltamethrin was positivelydetected in 13 broiler livers. It’s concluded that broiler livers that sold in Yogyakarta are detected to containdeltamethrin-contaminated.